Transformasi Identitas Perusahaan dalam Membangun Citra dan Reputasi : Studi Rebranding Azko - Kania Untari Salsabila; Fitria Ayuningtyas (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Corporate identity changes can be implemented over time and as the company grows. Before making any changes, companies must develop a well-thought-out communication planning strategy to ensure that the changes do not result in future losses, and the message conveyed in the communication strategy must be clear. Ace Hardware changed its name to Azko due to the expiration of its business contract. The rebranding process occurred gradually. Azko is committed to the change as an evolutionary development aimed at providing more optimal service. The purpose of this study was to determine the Azko rebranding process and its impact on the company's image and reputation. Using a literature study method, data was collected from reviewed literature, books, and journals. This study resulted in Azko's image and reputation being remarkably improved after the rebranding. This is evident in the continued presence of customers in Azko stores, and the successful communication of the rebranding strategy, ensuring the brand maintains its established image and reputation, and retains its loyal customers despite the name change.